liver abscess in an immunocompetent child - Jang-Mi Kwon; Hye Lim Jung; Jae Won Shim; Deok Soo Kim; Jung Yeon Shim; Moon Soo Park (Korean Pediatric Society, 2013)
Klebsiella pneumoniae has emerged as a leading pathogen that causes pyogenic liver abscesses (PLAs) in Korea. K. pneumoniae liver abscess (KLA) is potentially life threatening, and the diagnosis is difficult. In developed countries, PLA is rarely observed in children and is frequently associated with disorders of granulocyte function and previous abdominal infection. We observed a case of KLA in a healthy 12-year-old boy. To our knowledge, this is the first reported case of KLA in an immunocompetent child without an underlying disease in Korea. The patient was treated with percutaneous catheter drainage and antibiotics. The catheter was placed in the intrahepatic abscess for 3 weeks and parenteral antibiotics (ceftriaxone and amikacin) were administered for 4 weeks, followed by oral antibiotics (cefixime) for 2 weeks. We reported this case to raise awareness of KLA in immunocompetent children among physicians, and to review the diagnosis, risk factors, potential complications, and appropriate treatment of KLA.